Testing quark mixing in minimal left–right symmetric models with b-tags at the LHC - Andrew Fowlie; Luca Marzola (Nuclear Physics B, 2014)
Motivated by a hint in a CMS search for right-handed W-bosons in eejj final states, we propose an experimental test of quark-mixing matrices in a general left–right symmetric model, based on counting the numbers of b-tags from right-handed W-boson hadronic decays. We find that, with our test, differences between left- and right-handed quark-mixing matrices could be detected at the LHC with s=14 TeV. With an integrated luminosity of about 20/fb, our test is sensitive to right-handed quark-mixing angles as small as about 30° and with 3000/fb, our test's sensitivity improves to right-handed mixing angles as small as about 7.5°. Our test's sensitivity might be further enhanced by tuning b-tagging efficiency against purity.